Studi Hifa Eksternal CMA dalam Memahami Fungsinya Mengkontribusi Serapan P Tanaman Menggunakan Metode Thin Section - Machfud Effendy; Bhakti Wisnu Wijayani (UNIVERSITY OF LAMPUNG, 2008)
The study of the external hyphae of AMF was conducted for getting data of the soil hyphae distribution from the observation using thin section preparation. The experiment was arranged in factorial fully randomized design. The 1st factors are dosages of P application: 0; 45; 90; 135; and 180 kg ha-1. The second factor was AMF spore inoculation: with inoculation and without inoculation. The observations were conducted to roots and shoots oven dried, absorption of P, P32- fertilizer and P31 from soil. The soil was separated from T-pots and to prepare for making the thin section of soil for observation to hyphae distribution at every 2 cm level. The experiment results showed that the prepared of thin section was documented at the 200 µm x 200 µm (= 40.000 µm2) dimension can be used for external hifas observation. In the 400 µm2 areas of soil without AMF inoculated has about 24 to 27 external hyphal, so at the 40.000 µm2 areas has 2.400 until 2.700 hyphae. The soil was AMF inoculated has 19 to 25 hyphae at 400 µm2 areas of soil, and in the 40.000 µm2 areas has 1.900 until 2.500 hyphae and the length of hyphae about 67-75 m g-1. The diameter hifas at soil without AMF inoculation about 8-10 µm, and at the soil with AMF inoculated has hyphae diameter about 8-11 µm, and the long of hyphae about 53-69 m g-1. The growth speed of hyphae about 0.74-0.89 m day-1 or about 0.031-0.035 m hour-1. The inoculated plant with AMF spore gave more in contribution to P32 fertilizer and soil P31 than that in uninoculated plant, but the yield of shoot and root oven dried was higher for plants without inoculated AMF spore. The inoculated soil with spore of AMF caused to sum of AMF spore and soil P availability was higher than that in uninoculated soil.